The Agricultural Production and Food Industry Development Trends in the Context of Food Security of Russia - BOLDYREVA, Inna; ANDRYUSHCHENKO, Olga; NIKITAEVA, Anastasia; UDALOVA, Zoya; RUDASH, Janetta (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
Food security, in its function as an integral component of the state’s economic security, is one of the central issues of the state economic policy in most post-Soviet countries. Over the last decade, the food security policy implementation vectors have changed. While at the beginning of the market reforms, the key task of the former Soviet Union countries’ governments was to fill the food market, regardless of the import component, currently, food sovereignty is moving to the forefront, including the availability and quality of food. The present paper attempts to systematize and analyze factors and contradictions that affect the country’s food security. The scientific importance of the work is determined by the comprehensive system approach to the factor analysis of the agricultural sector operation from the perspective of the following aspects: the ongoing foreign policy of the state (the membership in the World Trade Organization and product embargo) and the state financial support mechanism for the agriculture.